Aplicación de la reparación civil como requisito para la suspensión de la ejecución de la pena: análisis de acuerdos plenarios y jurisprudencia - Mendoza Tejada, Evelyn Denisse (2019)
ABSTRACT The present investigation started from the study of civil reparation, of its nature in the criminal process, where it will be determined if it has a punitive or civil nature that is accessory to the penalty. For this a doctrinal and jurisprudential study of this institution was elaborated, addressing how it, in our system, is considered as a rule of conduct and at the same time as a requirement and condition for the suspension of the sentence. In the same sense, the case of the revocation of civil reparation as a rule of conduct in case of non-compliance was addressed, all from the doctrinal and jurisprudential study of the Peruvian penal system.